A generalized significance testing method for global measures of spatial association: an extension of the Mantel test. - Lee, Sang-Il (Environment & Planning A, 2004)
The Mantel test is extended in a way that provides a generalized significance testing method for global measures of spatial association. It is indicated that this extended Mantel test can be applied to any global measure of spatial association that has any form of spatial weights matrix in order to produce an approximation of the first two moments of the measures.